2004
DOI: 10.1021/ol048801k
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Reduction of Acyclic β-Alkoxy Ketones to Protected syn-1,3-Diols

Abstract: [reaction: see text] The conversion of 1-(2-methoxyethoxy)ethyl-protected beta-hydroxy ketones to syn-1,3-ethylidene acetals is effected by Et(3)SiH and SnCl(4). This reaction is proposed to proceed via a cyclic oxocarbenium ion intermediate and provides the products in yields that range from 69 to 94% and with diastereoselectivities that are >200:1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Later in 2004, Tarek Sammakia and coworkers developed a highly selectively reductive cyclization of acyclic b-alkoxy ketones using Et 3 SiH and SnCl 4 as the reagent system to yield protected syn-1,3-diols via an oxocarbenium intermediate, which consequently broadened the application of ionic hydrogenation method (Scheme 10). 32 It was found that the electronic and steric properties of the substituents had little effect on the yield and diastereoselectivity of the reaction. Various ketones can undergo the reaction in moderate to good yield and afforded >200 : 1 selectivity.…”
Section: Reduction Of C]o Bondmentioning
confidence: 99%
“…Later in 2004, Tarek Sammakia and coworkers developed a highly selectively reductive cyclization of acyclic b-alkoxy ketones using Et 3 SiH and SnCl 4 as the reagent system to yield protected syn-1,3-diols via an oxocarbenium intermediate, which consequently broadened the application of ionic hydrogenation method (Scheme 10). 32 It was found that the electronic and steric properties of the substituents had little effect on the yield and diastereoselectivity of the reaction. Various ketones can undergo the reaction in moderate to good yield and afforded >200 : 1 selectivity.…”
Section: Reduction Of C]o Bondmentioning
confidence: 99%
“…Similarly, the reaction of 1ac with acetaldehyde diethyl acetal provided a mixture of 1bc and 1b in a 5:1 ratio. This clearly indicates the reaction path that follows selective ionization of the acetal group . Apparently, the minimum amount of exchange is expected due to the involvement of an intimate ion pair of epoxonium ion ( II ) and the tethered alkoxide.…”
mentioning
confidence: 99%
“…(1) reduction of β-diketones or β-hydroxy ketones, 2,3 (2) reduction of R-hydroxy epoxides, 4 (3) radical-mediated C-H functionalization, 5 (4) highly selective reduction of acyclic β-alkoxy ketones, 6 and (5) silylmethyl radical cyclization of allylic alcohols. 7 Symmetrical and asymmetrical 1,3-diols can be obtained through the first two methods and last three methods, respectively.…”
mentioning
confidence: 99%
“…The 1,3-diol moiety is present in a number of natural products including polyene macrolide antibiotics, and has some biological activity . A number of conventional methods for the preparation of 1,3-diols have been developed, including: (1) reduction of β-diketones or β-hydroxy ketones, , (2) reduction of α-hydroxy epoxides, (3) radical-mediated C−H functionalization, (4) highly selective reduction of acyclic β-alkoxy ketones, and (5) silylmethyl radical cyclization of allylic alcohols . Symmetrical and asymmetrical 1,3-diols can be obtained through the first two methods and last three methods, respectively.…”
mentioning
confidence: 99%